CO2 Increase Experiments Using the CESM: Relationship to Climate Sensitivity and Comparison of CESM1 to CESM2. (11th November 2020) - Bacmeister, J. T.; Hannay, C.; Medeiros, B.; Gettelman, A.; Neale, R.; Fredriksen, H. B.; Lipscomb, W. H.; Simpson, I.; Bailey, D. A.; Holland, M.; Lindsay, K.; Otto‐Bliesner, B.
Abstract: We examine the response of the Community Earth System Model Versions 1 and 2 (CESM1 and CESM2) to abrupt quadrupling of atmospheric CO2 concentrations (4xCO2) and to 1% annually increasing CO2 concentrations (1%CO2). Different estimates of equilibrium climate sensitivity (ECS) for CESM1 and CESM2 are presented. All estimates show that the sensitivity of CESM2 has increased by 1.5 K or more over that of CESM1. At the same time the transient climate response (TCR) of CESM1 and CESM2 derived from 1%CO2 experiments has not changed significantly—2.1 K in CESM1 and 2.0 K in CESM2. Increased initial forcing as well as stronger shortwave radiation feedbacks are responsible for the increase in ECS seen in CESM2. A decomposition of regional radiation feedbacks and their contribution to global feedbacks shows that the Southern Ocean plays a key role in the overall behavior of 4xCO2 experiments, accounting for about 50% of the total shortwave feedback in both CESM1 and CESM2. The Southern Ocean is also responsible for around half of the increase in shortwave feedback between CESM1 and CESM2, with a comparable contribution arising over tropical ocean. Experiments using a thermodynamic slab‐ocean model (SOM) yield estimates of ECS that are in remarkable agreement with those from fully coupled Earth system model (ESM) experiments for the same level of CO2 increase. Finally, we show that the similarity of TCR in CESM1 and CESM2 masks significant regional differences in warming that occur in the 1%CO2 experiments for each model. Plain Language Summary: Computer models of the Earth's climate system are complex. Our best guess scenarios for how the climate system will change due to human activity over the next century are also complex. They include estimates of changing greenhouse gas (e.g., CO2 ) levels in the atmosphere, aerosol (e.g., smog and haze) emissions, and land use changes (e.g., deforestation and urbanization). To help understand this complex system, the climate modeling community has designed two simplified experiments: abrupt CO2 quadrupling (4xCO2) and 1% annual CO2 increase (1%CO2). In these experiments all human‐induced factors in the climate system are held constant (at preindustrial levels) except for CO2 in the atmosphere. Results of these experiments from different climate models can be compared to gain insight into the climate system. We look at two versions of the Community Earth System Model (CESM1 and CESM2). The warming simulated in the 4xCO2 experiment (climate sensitivity) has increased substantially in CESM2. This is related to changes in clouds over the Southern Ocean and tropics. At the same time warming in in the 1%CO2 experiment has not increased. This is related to differences in how CESM1 and CESM2 simulate northern oceans (Arctic, North Atlantic, and North Pacific). Key Points: Climate sensitivity has increased from 4 K to over 5 K in CESM2 compared to CESM1 Shortwave radiation feedbacks over the Southern Ocean play a key role in determining the response of CESM to increasing CO2 Various measures of climate response, including equilibrium climate sensitivity (ECS) and transient climate response (TCR), are not simply related in CESM